1992
DOI: 10.1086/648342
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococcus faecium in Hospitalized Children

Abstract: Vancomycin use may predispose to colonization with vancomycin-resistant E faecium. Vancomycin-resistant E faecium may be nosocomially spread. Contact isolation and restriction of vancomycin use may prevent spread of vancomycin-resistant E faecium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 17 publications
2
107
0
1
Order By: Relevance
“…Of the 2027 citations identified after literature searches, 12 were judged to meet our inclusion criteria and were included in this review [20,26-36]. All included studies presented pre- and post-intervention data, with the prevalence or incidence of VRE colonization and/or infection compared before and after implementation of a vancomycin use reduction intervention at the institution or ward under investigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 2027 citations identified after literature searches, 12 were judged to meet our inclusion criteria and were included in this review [20,26-36]. All included studies presented pre- and post-intervention data, with the prevalence or incidence of VRE colonization and/or infection compared before and after implementation of a vancomycin use reduction intervention at the institution or ward under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…All studies lacked a control group and none removed and reintroduced interventions. Eleven of 13 took place at a single teaching hospital [20,26-29,31-33,35,36], one was at a non-teaching community hospital [30] and one was a multi-center trial of both academic and community hospitals [34]. One study reported initial cases of VRE colonization [26], two reported current outbreaks without an endemic problem [27,28], and one reported a superimposed outbreak on an endemic problem with VRE infections [31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations